(untitled) (Journal of Applied Business and Economics, 2024)
Lagos State’s transformation into a critical urban hub highlights its economic promise and challenges, including rising unemployment, police brutality, and poverty amidst rapid growth. This study delves into how population increase, government spending, and financial policies affect the economy, revealing the critical role of education and job creation in tackling unemployment and enhancing living conditions. It underscores the impact of capital expenditure and monetary policies on economic stability, advocating for balanced development and targeted interventions to foster prosperity. The experience of Lagos offers valuable lessons for nationwide policy formulation and informed efforts for sustainable urban development and progress.